Evaluation of reference genes for quantitative expression analysis in Mylabris sibirica (Coleoptera, Meloidae) - Shen, Chen-Hui; Tang, Min; Li, Xiao-Fei; Zhu, Li; Li, Wei; Deng, Pan; Zhai, Qing; Wu, Gang; Yan, Xiao-Hong (Frontiers in Physiology, 2024)
Mylabris sibirica is a hypermetamorphic insect whose adults feed on oilseed rape. However, due to a shortage of effective and appropriate endogenous references, studies on molecular functional genes in Mylabris sibirica, have been tremendously limited. In this study, ten internal reference genes (ACT, ARF1, AK, EF1α, GAPDH, α-TUB, RPL6, RPL13, RPS3 and RPS18) were tested and assessed under four selected treatments including adult ages, adult tissues, temperatures, and sex by RT-qPCR based on five methods (Ct value, geNorm, NormFinder, BestKeeper and RefFinder). Our findings showed that RPL6 and RPL13 were the most optimal internal reference gene combination for gene expression during various adult ages and under diverse temperatures; The combination of RPL6 and RPS18 was recommended to test gene transcription levels under different adult tissues. AK and RPL6 were the best reference genes in male and female adults. RPL6 and RPL13 were the most appropriate reference gene pair to estimate gene expression levels under four different tested backgrounds. The relative transcript levels of a uridine diphosphate (UDP)-N-acetylglucosamine-pyrophosphorylase (MsUAP), varied greatly according to normalization with the two most- and least-suited reference genes. This study will lay the basis for further molecular physiology and biochemistry studies in M. sibirica, such as development, reproduction, sex differentiation, cold and heat resistance.